Technological Pedagogical Content Knowledge and Conventional Lecture Method: Comparative Effects on Biology Learning Outcomes - Iskeel Sina Raheem; Jelili Kehinde Tijani (Scientia Publica Media, 2026)
The persistent underachievement of students in biology in Nigeria has remained a source of concern, as conventional lecture methods are often unable to foster meaningful learning or sustain students’ interest in the subject. To address this gap, this study explored the effects of the Technological Pedagogical Content Knowledge (TPACK) instructional strategy and the Conventional Lecture Method (CLM) on students’ achievement and perception of biology, with gender included as a moderating factor. The study employed a quasi-experimental, pretest–posttest non-equivalent control group design. A sample of 337 Senior Secondary School II science and commercial students was drawn from six intact classes across public schools in Lagos State using a multistage sampling procedure. Two instruments, the Biology Achievement Test (BAT) and Students’ Perception of Biology Questionnaire (SPBQ), were administered, and the data were analysed using Analysis of Covariance (ANCOVA) at the 0.05 significance level. The results indicated that TPACK had a significant main effect on achievement, F(1, 332) = 28.67, p < .001, partial η² = .080, while gender also had a significant effect, F(1, 332) = 6.49, p = .011, partial η² = .019. A significant interaction between gender and instructional strategy was found on achievement, F(1, 332) = 8.59, p = .004, partial η² = .025. In terms of perception, strategy had a significant effect, F(1, 332) = 4.13, p = .043, partial η² = .012, and gender was also significant, F(1, 332) = 9.01, p = .003, partial η² = .026, but their interaction was not. The study concludes that TPACK enhances students’ achievement and perception in biology, though achievement gains varied by gender.